Epistemologi dan Pengembangan Ilmu Pengetahuan - Fariz Pari (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
This article wants to show that science based on positivism contains many weaknesses, which are proven by critics of positivism from Western philosophers, such as Karl Popper, Thomas Kuhn, Feyerabend and Rorty. The reaction of these figures placed them in a post-positivism flow, a movement of resistance to positivism in various domains ranging from ontology, epistemology to methodology. Thus, Islam can be an alternative offer to develop science.